Characterization of Streptococcus agalactiaeStrain TP540K and its potential as a target for DNA aptamer development in the preliminary Stage of Whole-Cell Based SELEX - Gan, ZiXuen; Tan, Pei Qin; Halim, Murni; Yasid, Nur Adeela; Yusof, Mohd Termizi; Hashim, Amalia Mohd; Abdullah, Jaafar; Rahman, Nik Mohd Afizan Nik Abd; Yasin, Ina Salwany Md; Hamzah, Firdaus Mohamad; Shukor, Mohd Yunus; Wasoh, Helmi (Hibiscus Publisher Enterprise, 2024)
Streptococcus outbreak caused mainly by Streptococcus agalactiaeleads to massive mortalities of freshwater aquatic organisms, especially cultured tilapias. This has caused a huge concern in the Malaysian aquaculture industry due to a lower aquaculture production affected by the outbreak. Thus, there is a need for a rapid and simple method to detect and monitor S. agalactiaein cultured fishponds. This study aims to investigate the characteristics of a local S. agalactiaestrain TP540K and its potential as a target bacterium to develop DNA aptamer through the whole-cell based ‘systematic evolution of ligands by exponential enrichment (SELEX)’ procedure. The morphology and biochemical characteristics of S. agalactiaestrain TP540K were studied. Furthermore, the preliminary stage of the SELEX process was carried out by incubating S. agalactiae strain TP540K with a single-stranded DNA library. In this study, S. agalactiae strain TP540K was confirmed to be spherical, gram-positive, catalase and oxidase-negative with beta-haemolytic characteristics. Additionally, the presence of bands with an estimated size of 80-90 base pairs on the agarose gel indicated the presence of DNA aptamer that could bind towards S. agalactiae strain TP540K during the SELEX process. The findings herein demonstrate that S. agalactiae strain TP540K has the potential to be utilised as a target for the production of DNA aptamers, and subsequent rounds of whole-cell based SELEX process can be performed to investigate the binding affinity and specificity for more accurate detection of S. agalactiae in a future application